PERCEPTIONS OF COLOSTOMY PATIENTS ABOUT NURSING CARE IN ONCOLOGY INPATIENT UNITS (Estima – Brazilian Journal of Enterostomal Therapy, 2021)
Objective: To analyze the perceptions of colorectal cancer patients using colostomy on the nursing care of the oncology inpatient units of a hospital in western Santa Catarina. Methods: Descriptive-exploratory study of qualitative approach carried out in the oncology inpatient units of the Hospital Regional do Oeste, in the period from January to August 2020, through a questionnaire containing sociodemographic data and semi-structured interview, applied to 20 patients with colorectal cancer using colostomy. The data were analyzed using Laurence Bardin’s Content Analysis. Results: The results indicated a prevalence of colostomy male patients, with a mean age of 60.25 years, married, retired, and with incomplete elementary education. From the qualitative analysis of the interviews emerged the category: patients’ perceptions of nursing care, which was subdivided into: nursing care with the bag and the stoma and nursing care during hospitalization. Conclusion: At the end of the survey, it is concluded that the colostomy patients perceive that the nursing staff performs the essential care of the bag and the stoma, including its exchange and hygiene during hospitalization, meeting the patients’ needs. In addition, they provide important guidance on the use of the devices, promoting health education.